Religion as Integration of Life - Aykara, Thomas (Journal of Dharma, 1983)
It is our firm belief that the Absolute unveils Himself in India, in the religious expressions of Indians, in and through the thought categories and life-patterns that convey the culture of India. Whatever be the religion we profess in India, it has to be through and through Indian in its expression. Religious consciousness is basically a co-consciousness. Every experience of ours is encapsuled in a particular expression which has its beauty and bounds. But an authentic experience of the Divine must help us break the shell of narrow communalism and selfish sectarianism. It is this profound conviction that made us concentrate more on the comparative study of religions and work for the integration and harmony of religions.